Production trial of Pleurotus sajor-caju (Indian oyster or phoenix) oyster mushroom - Maszlavér, P.; Győrfi, J. (International Journal of Horticultural Science, 2003)
Our experiments aimed at comparing the yields of the oyster mushroom hybrid Pleurotus HK 35 with those of the species Pleurotus sajor-caju on wheat straw. No data concerning the yields of the "Indian oyster" has so far been published in Hungary. The objective was, on the one hand, to discover what "phoenix" yields could be expected on 100 kg substrate, and on the other hand, to compare the yields with those of Pleurotus HK 35 which plays a dominant role in commercial production. We were also curious to know the amounts of harvest losses with the two mushrooms when picked with cut stems. It would be advisable to make progresses in developing production technology, especially in increasing yields. Considering that in its native place this species is able to provide yields even at temperatures of 22-28 °C, it seems possible that in hot summer months, as a shift from the hybrid HK 35, the production of the "Indian oyster" could be more economical.